Kinetic and kinematic differences between target and free kicking in taekwondo - Landeo, R.; McIntosh, A. S. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to evaluate the kinematic and kinetic (EMG) changes induced by varying kicking target sizes and the absence of these in Taekwondo kicking. Peak velocities and intersegmental timing and coordination variables were used to assess the kinematic of kicking executions. The kinetics of kicking executions were assessed from muscle co-contraction indexes obtained from EMG recording from selected muscles. Expert participants (n = 20) performed a set of ten Ap chagi (front kick) and Dollyo chagi (round house kick) to a set of target paddles of different sizes and masses. Significant differences were found between kicking conditions in the intersegmental timing of Ap chagi (p = 0.02) and Dollyo chagi (p = 0.04). Peak linear velocity of the ankle joint of Ap chagi (p = 0.63) and Dollyo chagi (p = 0.12) executions showed no significant differences. Differences in the thigh and leg angular velocities ratio were however significant for Ap chagi (p =0.01) and Dollyo chagi (p = 0.03) kicks. A strong correlation between muscle co-contraction and the mass of the kicking target (r = 0.95) was found.